NEED ANALYSIS OF INDONESIAN LANGUAGE TRAINING MATERIALS FOR FOREIGN WORKERS USING THE COMMUNICATIVE METHOD - Ade Mulyanah; Sariah Sariah; Rini Widiastuti; Nuny Sulistiany Idris; Exti Budihastuti; Nia Kurnia; Resti Nurfaidah (University of Kuningan, 2023)
There is no standardization of Indonesian language education and training for foreign workers (TKA), resulting in no training model that suits the needs of students. Therefore, this study aims to (1) describe the current condition of Indonesian language training for foreign workers by the Manpower Office; (2) identify Indonesian language training needs for foreign workers. The Ministry of Manpower has issued various regulations in this regard. This study uses a qualitative descriptive method through a communicative approach. The communicative approach forms the basis of the training model that will be developed because their main goal in learning Indonesian is to be able to communicate in their work environment. The data collection techniques used were interviews, surveys, and literature studies. The subject of this study is data on foreign workers in the Kepulauan Riau Province. The results of the study reveal two findings. Firstly, an overview of the current condition of Indonesian language training for foreign workers by the Manpower Office. Secondly, ) the identification of Indonesian language training needs for foreign workers . the data indicates that there is no standard training format yet.